Community treatment of latent tuberculosis in child and adult refugee populations: outcomes and successes - Harwood-Johnson, Emily; Leis, Karen S.; Hanson, Jacelyn; Olfert, Jordan; Blonde, Yvonne; Brindamour, Mahli (Frontiers in Public Health, 2023)
Background: Tuberculosis (TB) is the world's leading infectious cause of death, killing millions every year. In Canada, considered a low-incidence country for TB, the burden of TB disease is unequally distributed, and the majority of latent tuberculosis infections (LTBI) are experienced by newcomers from endemic regions. The purpose of this study was to measure LTBI treatment acceptance and completion outcomes at the REACH Clinic in Saskatoon, a local refugee clinic providing primary-care based LTBI management.Methods: A retrospective case series by sampling methodology was applied to review patients seen at the REACH Clinic from January 2017 to June 2021 and who had an IGRA or tuberculin skin test (TST) done for LTBI screening. Those with positive results were retained for analysis. LTBI treatment acceptance and completion groups were compared according to demographic variables, WHO regions of origin, year of arrival to Canada and LTBI treatment regimen.2 This is a provisional file, not the final typeset article Results: 523 patients were screened for LTBI and there were 125 positive tests, leading to a test positivity of 23.9%. The treatment acceptance rate was 84.8% and the treatment completion rate was 93.3%. All of those who declined treatment were more than 18 years of age (p-value 0.02). Otherwise, treatment acceptance and completion rates did not vary significantly by gender, categories of refugees, WHO region of origin, year of arrival to Canada or LTBI treatment regimen used.The refugee clinic acceptance and completion rates in this study are high and meet Canadian TB standards of care. The multidisciplinary clinic model and community support are important facilitators, which in combination with shorter treatment regimens, represent a path forward for LTBI management in refugees re-settling in low-incidence countries.